Relationship between Sleep Quality and Nurse Performance - Masruroh, Eny; Anggata, Amanda Anggata vera (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Nursing is one of the jobs with shift work rhythm. Shift work is one of the factors that affect sleep quality. Poor sleep quality is thought to have an impact on decreasing nurse performance, while one of the main factors that determines patient safety is nurse performance. The purpose of this study was to identify the relationship between sleep quality and nurse performance, especially in the inpatient room. The research method used correlation analysis with a cross-sectional approach with a sample of 35 nurses who were all inpatient ward nurses. Data collection was carried out by filling out the PSQI questionnaire and the nurse performance questionnaire. The analysis test used the Chi Square test. The results of this study showed that 30 respondents (85.7%) had poor sleep quality and 19 respondents (54.3%) had poor performance. The results of the analysis showed that there was a relationship between nurse sleep quality (p value = 0.008 <0.05). It can be concluded that poor sleep quality has the potential to reduce nurse performance. Therefore, interventions are needed to improve nurse sleep quality in order to improve their performance in providing health services.